Erster epileptischer Anfall und Epilepsien im Erwachsenenalter: Kurzfassung S2k-Leitlinie der Deutschen Gesellschaft für Neurologie in Zusammenarbeit mit der Deutschen Gesellschaft für Epileptologie - Holtkamp, Martin; May, Theodor W.; Berkenfeld, Ralf; Bien, Christian G.; Coban, Ingrid; Knake, Susanne; Michaelis, Rosa; Rémi, Jan; Seeck, Margitta; Surges, Rainer; Weber, Yvonne; Baum, Petra; et al. (Clinical Epileptology, 2024)
The new S2k guideline “First epileptic seizure and epilepsies in adulthood” provides recommendations on clinically relevant issues in five major topics: management of first epileptic seizures, pharmacotherapy, epilepsy surgery, complementary and supportive treatment, and psychosocial aspects. For the topic management of first epileptic seizures, the guideline provides recommendations on identifying the two major differential diagnoses, syncope and psychogenic non-epileptic seizure. The importance of additional examinations such as EEG, MRI and cerebrospinal fluid for syndromic classification and etiological allocation is discussed. Recommendations on neuropsychological and psychiatric screening tests are also given. The topic pharmacotherapy issues recommendations on antiseizure medication in monotherapy for focal, generalized and unclassified epilepsies; patient groups with special challenges such as the aged, women of childbearing potential and people with mental retardation are emphasized. Further issues are indications for measuring serum concentrations of antiseizure medication and possible risks of switching manufacturers. In the topic epilepsy surgery, indications for presurgical assessment and the multiple therapeutic approaches, such as resection, laser ablation, and neurostimulation are presented. Recommendations on postoperative management of patients, including rehabilitation and psychosocial counselling, are given. The topic complementary and supportive therapeutic approaches comprises recommendations on the diagnostics and treatment of common psychiatric comorbidities of epilepsy, such as anxiety disorder, depression and psychosis. Another important issue is the management of psychogenic non-epileptic seizures as a neuropsychiatric differential diagnosis or comorbidity of epileptic seizures. Furthermore, recommendations on the potential role of ketogenic diet and on acupuncture, homeopathy and other complementary approaches are made. The recommendations on psychosocial aspects comprise practical issues, such as fitness to drive a car, training and occupation, medical rehabilitation, sport, transition, patients’ self-help, education programs for patients and next of kin, adherence, advise on SUDEP.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Consensus; Epilepsy surgery; Pharmacotherapy; Psychosocial aspects; Recommendations